Factors Influencing Customer Satisfaction with Online Food Delivery Services in Lalitpur District (United Journal of Interdisciplinary Studies, 2024)
The digital transformation of the food industry has led to the proliferation of online food delivery services, making it crucial to understand the factors that influence customer satisfaction in this domain. This study aims to identify and comprehend these factors within Lalitpur Municipality, Nepal. The main objective of this research is to investigate the determinants of customer satisfaction with online food delivery services in Lalitpur Municipality. Employing a quantitative approach, this cross-sectional study utilized a judgmental sampling technique to select 110 respondents who had used online food delivery services in areas of Lalitpur Municipality, including Jawalakhel, Kumaripati, and Patan. Data was collected through self-administered questionnaires and analyzed using regression analysis. The theoretical framework guiding this study is the Expectancy Disconfirmation Theory (EDT). The findings revealed that while pricing did not demonstrate a significant positive relationship with customer satisfaction, factors such as ease of use, food quality, promotion, and privacy exhibited significant positive associations. Therefore, online food delivery services in Lalitpur Municipality should focus on enhancing the ease of use, food quality, promotional strategies, and privacy measures to improve customer satisfaction.